The Effect of Customer Experience on Guest Satisfaction and Loyalty: A Study on Digital Service-Based Hotels - Daimah, Daimah; Anwar, Saeful (Hospitality Management and Operations Journal, 2025)
Digital transformation in the hospitality industry has changed the way hotels provide services to guests, especially through the use of technologies such as self check-in, mobile applications, and Internet of Things (IoT) based systems. This study aims to analyze the influence of customer experience on guest satisfaction and loyalty in digital service-based hotels. Using a descriptive qualitative approach, data was collected through in-depth interviews with hotel managers, questionnaires to licensed employees, and observations of guest behavior at two digital hotels in Jakarta and Bali. The results show that a positive customer experience, characterized by ease of access, speed of service, and technological convenience, contributes greatly to guest satisfaction. Furthermore, high satisfaction drives loyalty in the form of return intentions and recommendations to others. However, human interaction is still required to maintain a balance between digital efficiency and emotional comfort. This research emphasizes the importance of integrative strategies in technology